Interactive Power Point Analysis as a Learning Media during Limited Face-to-Face Meeting in Class 1 SD Muhammadiyah 13 Surabaya - Nabila Ari Fatikha; Fajar Setiawan; Kunti Dian Ayu Afiani (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to analyze the interactive power point media used by teacher as learning media during limited face-to-face meetings in class I SD Muhammadiyah 13 Surabaya. This study used descriptive qualitative research method, research techniques of observation, interviews and documentation, the source of this data was shown to the principal, teacher and student. The results of this study indicated that the use of interactive power point media during learning in the era of limited face-to-face meetings is very helpful in increasing students' enthusiasm for learning by using interactive power point media, students' understanding of the material and students' ability to answer the questions given.